Optimalisasi Limbah Kulit Buah Menjadi Pupuk Organik Cair (POC) untuk Mendukung Pertanian Berkelanjutan di Desa Luthu Lamweu, Kecamatan Sukamakmur, Kabupaten Aceh Besar - Hisbullah, Hisbullah; Sy, Yuliana; Nasution, Fahrizal; Mahmuddin, Mahmuddin; Hakim, Lukman; Mulana, Farid; Ambarita, Aulia Chintia (Universitas Syiah Kuala, 2025)
Luthu Lamweu Village, located in Sukamakmur Subdistrict, Aceh Besar Regency, holds great potential for sustainable agricultural development but still faces challenges in managing household organic waste. Fruit peels, which are abundantly available, are often discarded without proper treatment, leading to potential environmental pollution. This community service program aimed to enhance the communitys understanding and skills in processing fruit peel waste into liquid organic fertilizer (LOF) beneficial for agriculture. The activities consisted of four main stages: preparation of materials and tools, participant education, hands-on LOF production practice, and monitoring of the fermentation process. Participants, mainly women from the PKK community group, were actively involved in each stage of the program. The results showed that the participants successfully produced LOF independently using simple materials and a two-week fermentation process, yielding a yellowish-brown liquid with a mild fermentation aroma. The final product was distributed to the participants and applied to home garden plants. This program effectively increased community awareness of organic waste management and supported environmentally friendly agricultural practices in Luthu Lamweu Village.